Depression, family support, and body mass index in Mexican adolescents - Caetano-Anolles, Kelsey; Teran-Garcia, Margarita; Raffaelli, Marcela; Alvarado Sánchez, Brenda; Mellado-Garrido, Miguel René (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2013)
The relationship between depressive symptomatology and elevated Body Mass Index (BMI), and between family support and low BMI is controversial. There are unanswered questions about the relationship between these three variables We tested the hypothesis that positive family support mediates the association between depression and bodyweight responsible for overweight and obesity in Mexican youth. We explored if family support correlated with depression and if depressive symptomatology correlated with obesity. Our results indicate that the relationship between depression and family support was significant (r = -0.44, p = 0.004). A significant relationship between depression and BMI was found only in women. When family support is included into the equation, the effect of depression on BMI disappeared. This observation indicates family support is a partial mediator between depression and obesity in adolescents. Our results are important and prompt an extended analysis of likely causative links between psychosocial parameters and health descriptors.